The Role of Knowledge Management in Improving Public Health Services - MAGBI Mimouna (University of Blida2-Faculty of Economics ,Business and Management Sciences, 2026)
Abstract: BACKGROUND: Enhancing service quality within health facilities remains a central objective, with the performance of healthcare professionals being a decisive factor. Knowledge management (KM) has emerged as a crucial mechanism for enhancing organizational efficiency and maintaining high-quality service delivery. Over the past decades, public health institutions have increasingly implemented KM frameworks to achieve optimal performance outcomes. This study aims to investigate the role of knowledge management in enhancing public health services at university hospital centers in Algeria. METHODS AND TOOLS: This study adopted a quantitative research approach, emphasizing numerical data and statistical analysis to produce objective and generalizable results. A cross-sectional survey design was employed, with primary data collected through a structured questionnaire. The questionnaire, considered the main instrument for data collection, consisted of 63 items organized into three principal axes. It was distributed to healthcare workers in the Algerian University Hospital Centers in both paper-based and electronic formats. The collected data were analyzed using JASP software, employing a range of statistical techniques to generate meaningful insights and ensure the reliability and validity of the findings. RESULTS: The main findings of the study indicate that: - There is a statistically significant relationship between knowledge management processes and the quality of public health services at the significance level (α≤0.05( - There is a statistically significant effect of knowledge management processes on the quality of public health services in Algerian University Hospital Centres at the significance level (α≤0.05). IV - Knowledge acquisition has no statistically significant effect on the quality of public health services in Algerian University Hospital Centres at the (α≤0.05) level. - Knowledge creation has a statistically significant effect on the quality of public health services in Algerian University Hospital Centres at the (α≤0.05) level. - Knowledge sharing has no statistically significant effect on the quality of public health services in Algerian University Hospital Centres at the (α≤0.05) level. - Knowledge storage has no statistically significant effect on the quality of public health services in Algerian University Hospital Centres at the (α≤0.05) level. - Knowledge application has a statistically significant effect on the quality of public health services in Algerian University Hospital Centres at the (α≤0.05) level. CONCLUSION: Processes of knowledge management, especially knowledge application and knowledge creation, are essential factors in improving the quality of healthcare services provided at the university hospital centres in Algeria. These findings emphasize the necessity of integrating structured KM strategies into institutional policies to enhance organisational and service quality. Future research should further investigate the mechanisms through which KM practices influence healthcare outcomes, with particular attention to contextual factors such as institutional culture, technological infrastructure, and workforce capacity. Such studies would help develop more sustainable and adaptable KM frameworks tailored to the needs of public health institutions in Algeria and similar settings. KEYWORDS: Knowledge management, Knowledge management processes, The quality of health service, Pubic health services, University Hospital Centres.
Case of Algeria
Keywords: Knowledge management; Knowledge management processes; the quality of health service; public health services; University Hospital Centres